A composite material for detecting H2S gas in lunar soil volatiles and its preparation method

By preparing the Ag2O@SnO2 composite material with core-shell structure, the problem of the difficulty in detecting H2S gas in volatilized lunar soil in the existing technology under low temperature and high vacuum environments is solved, and the gas detection effect with high sensitivity and rapid response in extreme environments is achieved.

CN115974138BActive Publication Date: 2025-03-14HUAZHONG UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211436219.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-16
Publication Date
2025-03-14
Estimated Expiration
2042-11-16

AI Technical Summary

Technical Problem

Existing semiconductor gas sensors are difficult to effectively detect H2S gas in volatile components of lunar soil under low temperature and high vacuum environments.

Method used

Ag2O@SnO2 composite material with core-shell structure is used to prepare SnO2 microspheres through hydrothermal reaction, and bind to Ag2O particles in an alkaline environment to form a loose and porous spherical structure to improve gas diffusion and reaction efficiency.

Benefits of technology

In extreme environments where low temperature -50℃ ≤T ≤-20℃ and high vacuum 10-5Pa ≤P ≤5Pa, the composite material can quickly and sensitively detect H2S gas, achieving effective detection of volatile components of lunar soil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115974138B_ABST
    Figure CN115974138B_ABST
Patent Text Reader

Abstract

The present invention proposes a composite material for detecting H2S gas in lunar soil volatiles and a preparation method thereof, wherein the preparation method comprises the following steps: S1, preparation of metal oxide semiconductor SnO2: mixing a tin salt solution and a chelating agent, obtaining a metal oxide semiconductor precursor product after a hydrothermal reaction, and calcining the metal oxide semiconductor precursor to obtain metal oxide semiconductor SnO2 powder; S2, preparation of composite material Ag2O@SnO2: mixing the metal oxide semiconductor SnO2 powder obtained in step S1 with a silver salt solution, adding an alkaline solution and stirring, centrifuging, washing, and drying to obtain composite material Ag2O@SnO2. The composite material Ag2O@SnO2 of the present invention can still be used to detect H2S in extreme environments such as low temperature and high vacuum, and has a fast response speed and extremely high sensitivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of semiconductor oxide technology, and in particular to a composite material for detecting H2S gas in lunar soil volatiles and a preparation method thereof. Background Art

[0002] Kinetic penetrating probes are an important mode and development direction for future extraterrestrial exploration. They refer to using pyrotechnics to allow probes to drill into a certain depth inside a planet, and are mainly used for atmospheric, geological environment, and water content detection. Volatile detection is one of the important exploration tasks of the probe, and its main goal is to measure the types and contents of volatiles (H2O, H2S, NH3, SO2, etc.) in the lunar soil at the South Pole of the Moon. If it is possible to dive into the lunar soil profile and conduct in-situ detection, data such as the comprehensive physical properties of the lunar soil suspected to contain water ice and the distribution of water ice materials in the depth profile will be obtained, which can provide the most direct evidence for revealing scientific issues such as the source of water materials on the moon, the state of occurrence of water materials, and the abundance of storage.

[0003] Semiconductor gas sensors are expected to be used in surveyors due to their high sensitivity, small size and light weight. Since volatile detection faces extreme environments such as high vacuum and low temperature, semiconductor gas sensors are currently used in high vacuum environments (10 -5 Pa or less), the oxygen anions on the semiconductor surface come from the aerobic environment and may diffuse and disappear under high vacuum; in a low temperature environment (the working environment of a reconnaissance missile is around -20°C), the carrier concentration and mobility inside the semiconductor material are reduced at low temperatures, which will affect the semiconductor material's high-sensitivity detection of gas (ppm level). The semiconductor gas sensor disclosed in the existing patent CN105223239A is used for high temperatures of 150-200°C and cannot be used in low temperature and high vacuum environments. Therefore, it is urgent to develop a semiconductor material for deep-space gas detection to achieve the detection of lunar soil volatiles. Summary of the invention

[0004] In view of this, the present invention proposes a composite material, a preparation method and an application thereof, which is suitable for low temperature and high vacuum environments and can detect H2S volatiles in lunar soil.

[0005] The technical solution of the present invention is implemented as follows: In the first aspect, the present invention provides a method for preparing a composite material for detecting H2S gas in lunar soil volatiles, comprising the following steps:

[0006] S1, preparation of metal oxide semiconductor SnO2: mixing tin salt and chelating agent, obtaining a metal oxide semiconductor precursor product after hydrothermal reaction, and calcining the metal oxide semiconductor precursor to obtain metal oxide semiconductor SnO2 powder;

[0007] S2. Preparation of composite material Ag2O@SnO2: mixing the metal oxide semiconductor SnO2 powder obtained in step S1 with silver salt, adding alkaline solution and stirring, centrifuging, washing and drying to obtain composite material Ag2O@SnO2;

[0008] The chelating agent is one or more combinations of citric acid monohydrate, ethylenediaminetetraacetic acid, tartaric acid and gluconic acid.

[0009] On the basis of the above technical solution, preferably, the tin salt is one or more combinations of stannous chloride, tin tetrachloride and stannous oxalate, and the silver salt is one or two combinations of silver nitrate and silver ammonia.

[0010] On the basis of the above technical solution, preferably, the molar ratio of the tin salt:chelating agent is 1 / 3 to 1 / 2.

[0011] On the basis of the above technical solution, preferably, the molar ratio of the silver salt to the metal oxide semiconductor SnO2 powder is 2 / 100 to 8 / 100.

[0012] In step S1, the hydrothermal reaction time is 6 to 24 hours, and the hydrothermal reaction temperature is 170 to 190°C.

[0013] On the basis of the above technical solution, preferably, in step S1, the calcination temperature of the metal oxide semiconductor precursor is 480-520°C, the calcination time is 1-3h, the heating rate is 4-6°C / min, and the cooling rate is 0.5-2°C / min.

[0014] On the basis of the above technical solution, preferably, in step S2, centrifugation is performed at a speed of 10000-12000 rpm for 5-10 min.

[0015] In a second aspect, the present invention provides a composite material for detecting H2S gas in lunar soil volatiles, wherein the composite material is Ag2O@SnO2 with a core-shell structure, wherein SnO2 is a loose and porous spherical structure.

[0016] On the basis of the above technical solution, preferably, the composite material is at a temperature of -50°C ≤ T ≤ -20°C and a vacuum degree of 10 -5 Detect H2S in an environment of Pa≤P≤5Pa.

[0017] The composite material for detecting H2S gas in lunar soil volatiles and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0018] (1) The composite material of the present invention has extremely high selectivity for H2S gas, which is mainly attributed to the selective adsorption of H2S gas by SnO2 microspheres in the composite material. When H2S gas is injected, the gas is more adsorbed by the surface of the "core"-SnO2 particles in the core-shell structure. Since the "shell"-Ag2O particles in the core-shell structure tightly wrap the SnO2 microspheres, they will come into contact with a large amount of H2S gas, and then react rapidly to generate a part of Ag2S with higher conductivity. Therefore, the overall resistance of the sensor decreases rapidly, that is, the response process of the Ag2O@SnO2 gas sensor to H2S under low temperature and high vacuum conditions is realized.

[0019] (2) The LP-SnO2-Ov microspheres obtained by adding the chelating agent are not only neatly arranged and well dispersed, but also have a large number of pores, which is very conducive to gas diffusion and gas-sensitive reaction.

[0020] (3) The composite material of the present invention can be used at low temperature -50°C ≤ T ≤ -20°C and high vacuum 10 -5 It can still be used to detect H2S in extreme environments such as Pa≤P≤5Pa, and it has a fast response speed and extremely high sensitivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 The scanning electron microscope images of the AO@SNO composite materials obtained in Examples 1 to 4 of the present invention;

[0023] Figure 2 This is a scanning electron microscope image of the loose porous SnO2 microspheres obtained in Comparative Example 1 of the present invention;

[0024] Figure 3 This is a scanning electron microscope image of the agglomerated SnO2 material obtained in Comparative Example 2 of the present invention;

[0025] Figure 4 1 is the gas-sensitive response curve of the AO@SNO composite material obtained in Examples 1 to 4 of the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] This embodiment describes in detail the composite material and the preparation method thereof, which includes the following steps:

[0029] S1. Preparation of oxide semiconductor SnO2: Weigh 2.26g SnCl2·2H2O and 4.20g C6H 10 O8·H2O was added to a beaker, 50 mL of anhydrous ethanol was added, and the mixture was stirred magnetically for 0.5 h. Then the mixed solution was transferred to a 100 mL hydrothermal reactor and reacted at 180 ° C for 12 h. After natural cooling, the generated powder was centrifuged and washed with water and ethanol for 3 times respectively, and then placed in an oven at 100 ° C for 12 h. Finally, the powder was transferred to a porcelain boat and placed in a muffle furnace for calcination at a calcination temperature of 500 ° C, a calcination time of 2 h, a heating rate of 5 ° C / min, and a cooling rate of 1 ° C / min to finally obtain SnO2 powder;

[0030] S2. Preparation of composite material Ag2O@SnO2: AgNO3 was weighed and dissolved in deionized water in a molar ratio of n(AgNO3):n(SnO2)=2:100. Excessive NaOH was added to generate AgOH, which was extremely unstable and immediately generated Ag2O precipitate and water. The final precipitate in the reaction was Ag2O. Since it was generated in an alkaline environment, deionized water was added and centrifuged to remove NaOH. + 、NO 3- OH - Then, 0.1 g of the previously synthesized SnO2 material was weighed and mixed with the generated Ag2O precipitate, and then centrifuged and dried to obtain the Ag2O@SnO2 composite material, which was labeled as 1AO@SNO.

[0031] Example 2

[0032] This embodiment describes in detail the composite material and the preparation method thereof, which includes the following steps:

[0033] S1. Preparation of oxide semiconductor SnO2: Weigh 2.26g SnCl4 and 6.0g EDTA in a beaker, add 50mL anhydrous ethanol, stir magnetically for 0.5h, then transfer the mixed solution to a 100mL hydrothermal reactor, react at 170℃ for 24h, and after natural cooling, centrifuge and wash the generated powder with water and ethanol for 3 times respectively, then dry it in an oven at 100℃ for 12h, finally transfer the powder to a porcelain boat, put it in a muffle furnace and calcine it at 480℃, calcination time is 3h, heating rate is 4℃ / min, cooling rate is 0.5℃ / min, and finally SnO2 powder is obtained;

[0034] S2. Preparation of composite material Ag2O@SnO2: Ag(NH3)2OH was weighed and dissolved in deionized water in a molar ratio of n(Ag(NH3)2OH):n(SnO2)=4:100. Excessive NaOH was added to generate AgOH, which was extremely unstable and immediately generated Ag2O precipitate with water. The final precipitate in the reaction was Ag2O. Since it was generated in an alkaline environment, deionized water was added and centrifuged to remove NaOH. + 、NO 3- OH - Then, 0.1 g of the previously synthesized SnO2 material was weighed and mixed with the generated Ag2O precipitate, and then centrifuged and dried to obtain an Ag2O@SnO2 composite material, which was labeled as 2AO@SNO.

[0035] Example 3

[0036] This embodiment describes in detail the composite material and the preparation method thereof, which includes the following steps:

[0037] S1. Preparation of oxide semiconductor SnO2: Weigh 2.26g of stannous oxalate and 4.80g of tartaric acid in a beaker, add 50mL of anhydrous ethanol, stir magnetically for 0.5h, then transfer the mixed solution to a 100mL hydrothermal reactor, react at 190℃ for 6h, and after natural cooling, centrifuge and wash the generated powder with water and ethanol for 3 times respectively, then place it in an oven at 100℃ for 12h, finally transfer the powder to a porcelain boat, put it in a muffle furnace for calcination, the calcination temperature is 520℃, the calcination time is 1h, the heating rate is 6℃ / min, and the cooling rate is 2℃ / min, finally obtaining SnO2 powder;

[0038] S2. Preparation of composite material Ag2O@SnO2: AgNO3 was weighed and dissolved in deionized water in a molar ratio of n(AgNO3):n(SnO2)=6:100. Excessive NaOH was added to generate AgOH, which was extremely unstable and immediately generated Ag2O precipitate and water. The final precipitate in the reaction was Ag2O. Since it was generated in an alkaline environment, deionized water was added and centrifuged to remove NaOH. + 、NO 3- OH - Then, 0.1 g of the previously synthesized SnO2 material was weighed and mixed with the generated Ag2O precipitate, and then centrifuged and dried to obtain the Ag2O@SnO2 composite material, which was labeled as 3AO@SNO.

[0039] Example 4

[0040] This embodiment describes in detail the composite material and the preparation method thereof, which includes the following steps:

[0041] S1. Preparation of oxide semiconductor SnO2: Weigh 2.26g SnCl2·2H2O and 4.20g gluconic acid in a beaker, add 50mL anhydrous ethanol, stir magnetically for 0.5h, then transfer the mixed solution to a 100mL hydrothermal reactor, react at 175℃ for 20h, and after natural cooling, centrifuge and wash the generated powder with water and ethanol for 3 times, then dry it in an oven at 100℃ for 12h, finally transfer the powder to a porcelain boat, put it in a muffle furnace and calcine it at 510℃, calcination time is 2.5h, heating rate is 5℃ / min, cooling rate is 1.5℃ / min, and finally SnO2 powder is obtained;

[0042] S2. Preparation of composite material Ag2O@SnO2: AgNO3 was weighed and dissolved in deionized water in a molar ratio of n(AgNO3):n(SnO2)=8:100. Excessive NaOH was added to generate AgOH, which was extremely unstable and immediately generated Ag2O precipitate and water. The final precipitate in the reaction was Ag2O. Since it was generated in an alkaline environment, deionized water was added and centrifuged to remove NaOH. + 、NO 3- OH - Then, 0.1 g of the previously synthesized SnO2 material was weighed and mixed with the generated Ag2O precipitate, and then centrifuged and dried to obtain the Ag2O@SnO2 composite material, which was labeled as 4AO@SNO.

[0043] Comparative Example 1

[0044] This embodiment describes an oxide semiconductor and a method for preparing the same in detail, including the following steps:

[0045] S1. Preparation of oxide semiconductor SnO2: Weigh 2.26g SnCl2·2H2O and 4.20g C6H 10 O8·H2O was placed in a beaker, 50 mL of anhydrous ethanol was added, and the mixture was stirred magnetically for 0.5 h. The mixed solution was then transferred to a 100 mL hydrothermal reactor and reacted at 180 ° C for 12 h. After natural cooling, the generated powder was centrifuged and washed with water and ethanol for 3 times respectively, and then dried in an oven at 100 ° C for 12 h. Finally, the powder was transferred to a porcelain boat and calcined in a muffle furnace at a calcination temperature of 500 ° C for 2 h. The heating rate was 5 ° C / min and the cooling rate was 1 ° C / min to finally obtain SnO2 powder monomer.

[0046] Comparative Example 2

[0047] This embodiment describes an oxide semiconductor and a method for preparing the same in detail, including the following steps:

[0048] S1. Preparation of oxide semiconductor SnO2: Weigh 2.26 g SnCl2·2H2O into a beaker, add 50 mL anhydrous ethanol, stir magnetically for 0.5 h, then transfer the mixed solution to a 100 mL hydrothermal reactor, react at 180°C for 12 h, and after natural cooling, centrifuge and wash the generated powder with water and ethanol for 3 times respectively, then dry it in an oven at 100°C for 12 h, finally transfer the powder to a porcelain boat, put it in a muffle furnace and calcine it at 500°C for 2 h, the heating rate is 5°C / min, the cooling rate is 1°C / min, and finally SnO2 powder monomer is obtained.

[0049] like Figure 1 As shown in the SEM morphology of the composite materials in Examples 1 to 4 of the present invention, it can be seen that the morphology of the composite materials is a core-shell structure; Figure 2 As shown in Figure 3, the morphology of SnO2 is a loose and porous spherical structure. Figure 4 As shown in the figure, the morphology of SnO2 in comparative example 2 is agglomerates, which shows that the SnO2 synthesized without chelating agent is seriously aggregated, which is not conducive to the exposure of active sites of gas-sensitive materials. The LP-SnO2-Ov microspheres finally obtained by adding chelating agent are not only neatly arranged and well dispersed, but also have more holes, which is very conducive to the diffusion of gas and the conduct of gas-sensitive reaction.

[0050] The application of the composite material in the embodiment of the present invention to detect lunar soil volatiles is described in detail below:

[0051] The nAO@SNO composite materials with different Ag2O contents (specifically including 1AO@SNO, 2AO@SNO, 3AO@SNO, and 4AO@SNO) were used as sensitive materials to make MEMS gas sensors and placed at -20°C with 1×10 -5 The test was carried out in a low temperature and high vacuum test chamber of Pa.

[0052] like Figure 3 As shown in the figure, when 1ppm H2S gas is injected, we can see that the 1AO@SNO gas sensor has almost no response. This may be because the content of Ag2O in the 1AO@SNO composite material is too little, resulting in the slight resistance drop being offset by the resistance increase caused by the pressure change, so there is no obvious response. The response value of the 2AO@SNO gas sensor is 7.6, and as the content of Ag2O in the AO@SNO composite material increases, its response value also increases significantly. The response values ​​of the 3AO@SNO and 4AO@SNO gas sensors are 43.6 and 107.7, respectively. It is worth noting that as the content of Ag2O in the AO@SNO composite material increases, its response speed shows a significant decreasing trend. The response time of the 2AO@SNO gas sensor is 15.3s, while the response times of the 3AO@SNO and 4AO@SNO gas sensors are 87.5s and 201.3s, respectively. This may be because the Ag2O content in the 3AO@SNO and 4AO@SNO composite materials is too high, resulting in agglomeration, which leads to slow diffusion of gas between Ag2O particles. The response speed is an important indicator in the detection of lunar soil volatiles, so 2AO@SNO has relatively better gas-sensing performance.

[0053] In this application, the gas-sensitive working mechanism of Ag2O@SnO2 is to utilize the synergistic effect of its core-shell structure, with SnO2 loose porous microspheres as the "core" to adsorb H2S gas under low temperature and high vacuum conditions, and Ag2O nanoparticles as the "shell" to chemically react with the H2S gas adsorbed on the surface of the SnO2 loose porous microspheres under low temperature and high vacuum conditions to generate Ag2S with lower conductivity, thereby achieving the response of the gas sensor.

[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite material for detecting H2S gas in lunar soil volatiles, characterized in that: The steps include: S1, preparation of metal oxide semiconductor SnO2: mixing tin salt and chelating agent, obtaining a metal oxide semiconductor precursor product after hydrothermal reaction, and calcining the metal oxide semiconductor precursor to obtain metal oxide semiconductor SnO2 powder; S2. Preparation of composite material Ag2O@SnO2: mixing the metal oxide semiconductor SnO2 powder obtained in step S1 with silver salt, adding alkaline solution and stirring, centrifuging, washing and drying to obtain composite material Ag2O@SnO2; The molar ratio of the silver salt to the metal oxide semiconductor SnO2 powder is 4 / 100 to 8 / 100; The composite material is subjected to a temperature of -50°C ≤ T ≤ -20°C and a vacuum degree of 10 -5 Detect H2S in an environment of Pa≤P≤5Pa; The composite material is Ag2O@SnO2 with a core-shell structure, wherein SnO2 is a loose and porous spherical structure.

2. The method for preparing a composite material for detecting H2S gas in lunar soil volatiles according to claim 1, characterized in that: The chelating agent is one or more combinations of citric acid monohydrate, ethylenediaminetetraacetic acid, tartaric acid and gluconic acid.

3. The method for preparing a composite material for detecting H2S gas in lunar soil volatiles according to claim 1, characterized in that: The tin salt is one or more combinations of stannous chloride, tin tetrachloride and stannous oxalate, and the silver salt is one or two combinations of silver nitrate and silver ammonia.

4. The method for preparing a composite material for detecting H2S gas in lunar soil volatiles according to claim 1, characterized in that: The molar ratio of the tin salt to the chelating agent is 1 / 3 to 1 / 2.

5. The method for preparing a composite material for detecting H2S gas in lunar soil volatiles according to claim 1, characterized in that: In step S1, the time of the hydrothermal reaction is 6 to 24 hours, and the temperature of the hydrothermal reaction is 170 to 190°C.

6. The method for preparing a composite material for detecting H2S gas in lunar soil volatiles according to claim 1, characterized in that: In step S1, the calcination temperature of the metal oxide semiconductor precursor is 480-520°C, the calcination time is 1-3h, the heating rate is 4-6°C / min, and the cooling rate is 0.5-2°C / min.

7. The method for preparing a composite material for detecting H2S gas in lunar soil volatiles according to claim 1, characterized in that: In step S2, centrifuge at 10000-12000 rpm for 5-10 min.

Citation Information

Patent Citations

  • Ag / Ag2O-modified SnO2 porous composite and application of Ag / Ag2O-modified SnO2 porous composite to hydrogen detection

    CN105223239A